OUR WHITE HOUSE : LOOKING IN, LOOKING OUT - National Children's Book and Literacy Alliance (Somerville, Mass. : Candlewick Press, 2010)
Presents a compilation of essays, personal accounts, historical fiction, and poetry about the White House in each period of American history